Filling gaps in the knowledge of the Colombian Darwin wasps (Hymenoptera: Ichneumonidae): new records, description of unknown males, and taxonomical notes - Pádua, Diego G.; Fernandes, Daniell R.r.; Araujo, Rodrigo O.; Mazariegos, Luis A. (Zootaxa, 2023)
Darwin wasps (Hymenoptera: Ichneumonidae) are parasitoids and a natural enemy of a wide range of holometabolous insects and spiders and are considered one of the largest families in the animal kingdom. Unfortunately, there are great gaps in the knowledge of this family in Colombia. This study aims to expand the knowledge of Darwin wasps in Colombia, through new records for the country and especially the department of Antioquia. We present the diagnosis and digital images of the recorded species, and we describe for the first time the males of three species of Dolichomitus Smith, 1877: D. mariajosae Araujo & Pádua, 2020; D. menai Araujo & Pádua, 2020; D. orejuelai Araujo & Pádua, 2020.